2009
DOI: 10.1007/s10600-009-9404-0
|View full text |Cite
|
Sign up to set email alerts
|

Microwave–assisted extraction and identification of polysaccharide from Lycoris aurea

Abstract: Three polysaccharide fractions were separated from the extract of Lycoris aurea using DEAE-52 and Sephadex G-150 column chromatography. FT-IR spectroscopy revealed the typical characteristics of polysaccharide fractions. The molecular weights of three polysaccharides were characterized by HPGFC, which were 31.9 kDa, 35.7 kDa, and 72.7 kDa, respectively. Their chemical compositions were also studied. The conditions for microwave-assisted extraction (MAE) of polysaccharide from L. aurea were investigated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the case of Cordyceps militaris, the optimal conditions to obtain the highest polysaccharide yield were a microwave power of 744.8 W for 4.2 min and a ratio of solution to solid of 31.1 mL/g [19]. Similarly, three polysaccharide fractions were separated from Lycoris aurea [20].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…In the case of Cordyceps militaris, the optimal conditions to obtain the highest polysaccharide yield were a microwave power of 744.8 W for 4.2 min and a ratio of solution to solid of 31.1 mL/g [19]. Similarly, three polysaccharide fractions were separated from Lycoris aurea [20].…”
Section: Microwave-assisted Extractionmentioning
confidence: 99%
“…Polysaccharides, another important component, are also present in large amounts in the Amaryllidaceace family, especially in the bulb. Our laboratory found that the bulb of L. aurea contained, depending on the seasons, from 10.87% to 37.44% polysaccharides (per fresh weight) [4]. However, to the best of our knowledge, there are no published reports related on the bioactivities activities of alkaloids and polysaccharides from L. aurea bulbs.…”
Section: Introductionmentioning
confidence: 86%
“…It was necessary to select the parameters that had major effects (Bagherian et al, 2011;. It was reported that extraction power, extraction temperature, extraction time, ratio of water to raw material and extraction number had significant effects on the polysaccharides (Ru et al, 2009;Bagherian et al, 2011;Zhao et al, 2013). While Microwave power, extraction time and ratio of water to raw material were regards as the critical influencing factors in MAE (Ru et al, 2009;Zhao et al, 2013).…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
“…It was reported that extraction power, extraction temperature, extraction time, ratio of water to raw material and extraction number had significant effects on the polysaccharides (Ru et al, 2009;Bagherian et al, 2011;Zhao et al, 2013). While Microwave power, extraction time and ratio of water to raw material were regards as the critical influencing factors in MAE (Ru et al, 2009;Zhao et al, 2013). So the three parameters were screened by single-factor experiment including X 1 (microwave power, 100 _ 600 W), X 2 (extraction time, 2.5 _ 15 min), and X 3 (W/M ratio, 10 _ 60 mL/g), and extraction was repeated 3 times in this experiment.…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation